Driving Business Models Toward Sustainability in Arctic Nature Tourism - Sahebalzamani,Samira (Associação Nacional de Pós-Graduação e Pesquisa em Administração)
ABSTRACT Context: research into sustainability as a highly debated concept has become widespread and given rise to a diverse and interesting arena in the management literature in which the relevance of business models is extensively acknowledged. Objective: by integrating sustainability into the business model concept, this study attempts to determine how business models are driven toward sustainability. Methods: a qualitative multiple-case approach is applied to scrutinize five small/micro companies offering nature-based activities in Arctic Norway. Results: four internal and six external drivers are found crucial to incorporating sustainability in business models. Conclusion: the findings contribute to the field of sustainable business models by deepening the understanding of how specific internal and external drivers operate across different business models. Moreover, business models are driven toward sustainability differently, depending on the extent to which sustainability is embedded into them.